A site of struggle - Fernández, Silvana Noelí (1999)
Two of the main justifications for concentrating on Chinua Achebe's Things Fall Apart and No Longer at Ease are that the symptomatic3 reading of these two texts will reveal how the use of language incorporates the warning that the site of the ‘shared ' discourse-the literary text- is not the site of a shared mental experience and how the construction of counter-hegemonies is in part contingent on the very structure of language itself.